PEMIKIRAN HUKUM EKONOMI ISLAM PERSPEKTIF AL-GHAZALI - Hidayat, Didin (LPPM STAI Al-Azhary Cianjur, 2023)
Al-Ghazali's thought had a great influence on the Islamic world and continues to be widely read and quoted today. Thanks to his services, the discipline of logic or philosophy became the maestro of thinking in the Islamic world. Al-Ghazali's thoughts also cover muamalat or business and economic practices including the value of exchange (barter), business evolution and market evolution, as well as economic thinking that prioritizes maslahah which covers all human activities. Al-Ghazali said the most important thing about muamalat is that everything that is done in this world is for eternal life in the hereafter. A Muslim's business must have a broad orientation related to the world and the hereafter. Al-Ghazali has described all problems in the form of both mashâlih and mafâsid which aim to improve social welfare. In addition, Al-Ghazali argues that socio-economics is based on a concept called the social welfare function (Mashlahah). In economic and business practices, Al-Ghazali recommends that economists or business people pay attention to moral issues in doing business. For al-Ghazali, the prohibition of usury is absolute. The argument he put forward is not only as a sin, but gives the possibility of exploitation and injustice in the transaction.